Spinal cord dorsal horn sensory gate in preclinical models of chemotherapy-induced painful neuropathy and contact dermatitis chronic itch becomes less leaky with Kcc2 gene expression-enhancing treatments - Yeo, Michele; Zhang, Qiaojuan; Ding, LeAnne; Shen, Xiangjun; Chen, Yong; Liedtke, Wolfgang (Frontiers in Molecular Neuroscience, 2022)
Low intraneuronal chloride in spinal cord dorsal horn (SCDH) pain relay neurons is of critical relevance for physiological transmission of primary sensory afferents because low intraneuronal chloride dictates GABA-ergic and glycin-ergic neurotransmission to be inhibitory. If neuronal chloride rises to unphysiological levels, the primary sensory gate in the spinal cord dorsal horn becomes corrupted, with resulting behavioral hallmarks of hypersensitivity and allodynia, for example in pathological pain. Low chloride in spinal cord dorsal horn neurons relies on the robust gene expression of Kcc2 and sustained transporter function of the KCC2 chloride-extruding electroneutral transporter. Based on a recent report where we characterized the GSK3-inhibitory small molecule, kenpaullone, as a Kcc2 gene expression-enhancer that potently repaired diminished Kcc2 expression and KCC2 transporter function in SCDH pain relay neurons, we extend our recent findings by reporting (i) effective pain control in a preclinical model of taxol-induced painful peripheral neuropathy that was accomplished by topical application of a TRPV4/TRPA1 dual-inhibitory compound (compound 16-8), and was associated with the repair of diminished Kcc2 gene expression in the SCDH; and (ii) potent functioning of kenpaullone as an antipruritic in a DNFB contact dermatitis preclinical model. These observations suggest that effective peripheral treatment of chemotherapy-induced painful peripheral neuropathy impacts the pain-transmitting neural circuit in the SCDH in a beneficial manner by enhancing Kcc2 gene expression, and that chronic pruritus might be relayed in the primary sensory gate of the spinal cord, following similar principles as pathological pain, specifically relating to the critical functioning of Kcc2 gene expression and the KCC2 transporter function.